2013
DOI: 10.1097/mrr.0b013e32835c79ea
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to difficulties with employment in patients with multiple sclerosis

Abstract: We assess the knowledge available on the difficulties experienced by multiple sclerosis (MS) patients in work-related activities. A literature review was carried out using the keywords 'multiple sclerosis' and 'employment' or 'work' through PubMed and EMBASE. Papers reporting patient-derived data on difficulties at work as primary or secondary outcome measures and published in the period 2002-December 2011 were searched. A total of 26 papers were selected, for a total of 32 507 patients (mean age 46.2 years; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 33 publications
3
80
0
Order By: Relevance
“…Those expecting to reduce their job responsibilities perceived themselves as more severely disabled from their MS symptoms and as more constrained by lack of accessible housing. Adults with MS expecting to exit the workforce in 2 to 5 years presented a profile consistent with the literature pertaining to predictors of employment and unemployment (Honarmand, Akbar, Kou, & Feinstein, 2011;Moore et al, 2013;Schiavelin et al, 2013;Smith & Arnett, 2005). They were older and perceived that they were affected more severely by their MS symptoms, particularly as those symptoms affected their mobility, which is consistent with findings that unemployed adults with MS had the highest level of incapacity in comparisons with employed adults with MS (full-time or part-time).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Those expecting to reduce their job responsibilities perceived themselves as more severely disabled from their MS symptoms and as more constrained by lack of accessible housing. Adults with MS expecting to exit the workforce in 2 to 5 years presented a profile consistent with the literature pertaining to predictors of employment and unemployment (Honarmand, Akbar, Kou, & Feinstein, 2011;Moore et al, 2013;Schiavelin et al, 2013;Smith & Arnett, 2005). They were older and perceived that they were affected more severely by their MS symptoms, particularly as those symptoms affected their mobility, which is consistent with findings that unemployed adults with MS had the highest level of incapacity in comparisons with employed adults with MS (full-time or part-time).…”
Section: Discussionsupporting
confidence: 79%
“…Occurring typically in the peak years of a person's career development, MS is characterized by a wide variety of symptoms ranging from diffuse fatigue to cognitive limitations (Schiavelin et al, 2013). In too many cases, MS, like many chronic illnesses, results in premature exit from the workforce due to both the complexity and unpredictable nature of its symptoms (Antao et al, 2013;Krause, Kern, Horntrich, & Ziemssen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lower scores of energy subscale in female and married patients were expected as these groups have more responsibilities in daily life. Higher scores of all the subscales of MMMS in educated and working group is a comparable result reported in many quality of life studies (2,31,32). Lower mean scores on the MMMS scores for SPMS participants compared to RRMS participants further supports the construct validity of the MMMS scale.…”
Section: Discussionsupporting
confidence: 65%
“…Age, gender, education have also been variably found to predict employment status in PwMS [6,12,[14][15][16]. Some studies showed clinical factors as MS-related symptoms, MS form, disability, disease duration have been found to predict employment status [12][13][14][15]17]. Other factors, which have been explored and found to be predictive of employment outcomes in published studies, included mostly job characteristics [18].…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies showed that both demographic variables, disease-related and workplace-related factors play a role in employment's loss by people with MS [13]. Age, gender, education have also been variably found to predict employment status in PwMS [6,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 97%